Fenomena Globalize the Intifada di Tengah Genosida Warga Palestina - Saskia Aulia Putri; Nur Isdah Idris (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2024)
In the recesses of the Palestine-Israel conflict which continues to metamorphose, the Intifada movement has become a symbol of resistance to occupation and oppression which curbs the aspirations of the Palestinian people. However, in this era of increasingly connected globalization, the dynamics of this movement are experiencing a significant transformation, which challenges traditional paradigms and brings new challenges that affect both parties. With major challenges such as perceived injustice and political instability, resolving this conflict has the potential to reduce extremism and increase stability in the Middle East, so this study will explore how the Palestinian Intifada influenced conflict resolution efforts with the aim of understanding the essence of the Intifada movement which is often seen as a form of extremism and radicalization, and this study will also explore the transformation of the Palestinian Intifada into a global phenomenon, considering its impact on conflict dynamics and practical approaches to achieving sustainable and stable peace in the region.